A community EQUIP treatment group. Issue 2 (11th June 2018) - Tearle, Shaw; Holt, Rachel R.
Abstract : Purpose: There is a pressing need to develop community forensic support for adults with intellectual disabilities and a high risk to others. Equipping youth to help one another (EQUIP) was developed for juvenile offenders in the USA and is used across Europe and North America. The purpose of this paper is to evaluate an adapted community model of EQUIP for men with intellectual disabilities and a history of sexual offending. Design/methodology/approach: A case series design was used. The adapted EQUIP group ran for one session per week over ten months, with each participant accompanied by a support worker. Six men living in the community with intellectual disabilities and a history of sexual offending completed the programme. Findings: Analysis of the results suggests that this adapted version of EQUIP produced similar results to the programme delivered in an inpatient setting. Participants' reasoning and problem-solving abilities were improved post-intervention. Satisfaction levels from participant and their support workers were high. There was no evidence of recidivism during the ten months the group ran. Research limitations/implications: The case series design utilised only allows the conclusion that the changes above occurred at the same time as the group. Further research is needed to ascertain whether it is likely that the intervention resulted in the changes. Practical implications: There is a pressing need to develop the evidence base for interventions offered in the community to people with intellectual disabilities and a history of offending. This study provides some evidence that EQUIP can be adapted to suit this population. Social implications: The availability of community interventions may, over time, decrease the need for detention in inpatient settings. This is in line with the transforming care agenda. Originality/value: This is the first published research into use of EQUIP in the community with adult participants with intellectual disabilities.